STRATEGI KOMUNIKASI BEAUTY INFLUENCER PADA AKUN @LAILAUUL DALAM MEMBANGUN PERSONAL BRANDING DI MEDIA SOSIAL INSTAGRAM - Yeni Febriyanti; Achmad Nashrudin; April Laksana; Noerma Kurnia Fajarwati; Putri Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of social media has led to the emergence of influencer s who build personal branding through various digital platforms, particularly Instagram. In relation to this phenomeon, the Instagram account @lailauul, owned by Aulia Laela, is noteworthy due to its success in forming a substantial audience through beauty-related content. This study aims to analyze the communication strategies employed by the beauty influencer in building personal branding and to identify the related challenges and solutions. This research uses a descriptive qualitative approach and applies Hubert K. Rampersad’s theory of Authentic Personal Branding, which consists of eleven key indicators: authenticity, integrity, consistency, specialization, authority, distinctiveness, relevance, visibility, persistence, goodwill, and performance. Data were obtained through in-depth interviews, observation, and documentation of digital communication activities on the @lailauul Instagram account. The findings show that Aulia Laela builds her personal branding authentically through consistent and relevant content that reflects her genuine personality. Challenges such as algorithm changes and content fatigue were managed through adaptive strategies and flexible scheduling. This study suggests that beauty influencer s should maintain authenticity, actively engage with their audience, and continuously adapt their content to audience interests in order to remain relevant and trustworthy.